1984
DOI: 10.2136/sssaj1984.03615995004800060003x
|View full text |Cite
|
Sign up to set email alerts
|

Cone Index of Loamy Sands as Influenced by Pore Size Distribution and Effective Stress

Abstract: Tillage pans form in coarse textured soil horizons of the Atlantic Coastal Plain and develop high cone index values (soil strengths) which slow root growth and may decrease crop yields. Identification of soil properties that influence cone index may improve field identification of tillage pans and lead to the development of techniques to reduce their detrimental effects. This study examined the influence of pore size distribution, and effective stress on the cone index of loamy sand and loamy fine sand soil ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
18

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 0 publications
5
22
0
18
Order By: Relevance
“…particles (Vepraskas, 1984). This confirms the structural differences observed between the soil samples due to machinery traffic within the experimental area.…”
Section: Soil Resistance To Penetrationsupporting
confidence: 83%
See 1 more Smart Citation
“…particles (Vepraskas, 1984). This confirms the structural differences observed between the soil samples due to machinery traffic within the experimental area.…”
Section: Soil Resistance To Penetrationsupporting
confidence: 83%
“…It can be observed that BD had a great impact on PR = 2 MPa values, whose magnitude also depended on soil drying. Thus, in the crop rows, where the lowest BD values indicate decreased cohesion and friction forces between soil particles (Vepraskas, 1984), there will be less physical constraints for plant growth with more soil drying than in-between crop rows. Due to this wide variability in BD values, in which PR = 2 MPa, these results agree with findings by Letey (1985) that this physical property influences plant growth indirectly, and should therefore not be used alone to evaluate the effect of management practices on physical soil quality.…”
Section: Soil Resistance To Penetrationmentioning
confidence: 99%
“…O aumento da RP com o decréscimo de θ pode ser associado à maior coesão entre as partículas minerais particularmente em solos de textura argilosa (Kay & Angers, 1999). Com o incremento da Ds, tanto a maior fricção entre as partículas quanto a maior coesão atuam como os principais mecanismos para o aumento da RP (Vepraskas, 1984). A influência positiva da Ds sobre a CRA pode ser atribuída à redistribuição do tamanho de poros com aumento na proporção de poros de menor diâmetro, de modo a se tornarem mais eficientes na retenção de água em elevados Ψ. Em baixos Ψ, a influência da Ds sobre a CRA pode ser atribuída à maior massa de sólidos com elevada superfície de adsorção, uma vez que a compactação geralmente não altera a microporosidade dentro dos agregados.…”
Section: Resultsunclassified
“…A RP variou positivamente com Ds e negativamente com θ, em acordo com os resultados reportados por Silva et al (1994), Tormena et al (1998Tormena et al ( , 1999, Imhoff et al (2001) e Leão et al (2004). O aumento de RP com a Ds pode ser atribuído ao efeito da compactação do solo, o que, segundo Vepraskas (1984), resulta num maior contato ou fricção interpartículas. Contrariamente, a redução de RP com θ deve-se ao efeito lubrificante da água, que reduz a coesão entre as partículas na matriz do solo.…”
Section: Resultsunclassified